Do minority acquisitions relieve financial constraints? - Macoris, Lucas Serrão (2018)
This study intends to examine the occurrence and effectiveness of minority block transactions in the presence of financial constraints in target firms. Minority transactions represent a strategic decision with specific characteristics if compared to the various forms of integration. In fact, several authors claim that minority block transactions may represent an alternative to alleviate financial constraints. However, there are still few studies that empirically address the relationship between financial constraints and the occurrence of such transactions. More specifically, there is no empirical evidence that states that minority transactions actually ease targets\' financial restrictions and foster corporate investment. Using a panel composed of approximately 12.000 deals, results show a positive relationship between the presence of financial constraints in target firms and the occurrence of minority transactions. Moreover, there is a significant difference between on the growth of investment and leverage indicators of target firms\' related to its counterfactuals after deal completion, indicating the effectiveness of minority transactions in alleviating such companies\' restrictions.